Spatial analysis of the characteristics of rural women in Shatra District in 2023 - dr.Ahmed Baqir Juma (Journal of College of Education, 2024)
This study examined the characteristics of rural women in Shatra District for the year 2023, because women have an important and pivotal role that they play in achieving rural development. They participate with men in several tasks, such as participating in the field, raising livestock, raising children, preparing food, and doing household chores, which requires paying attention to them and giving them more experience and skill. In order to be able to perform most of the roles entrusted to her with all care and precision, the study touched on revealing the characteristics of rural women in the Shatrah district and the variation of these characteristics at the level of administrative units, as well as knowing the most prominent problems they face. This study relied on field work in the study area for the year 2023, in addition to data on population estimates for the year 2022, as well as the population census for the year 1997, and population estimates for Dhi Qar Governorate for the years (2016-2023), in addition to relying on data from official government departments and office sources, as well as relying on statistical methods and GIS programs for drawing maps. The study reached a group Among the most important results is that there is an increase in the size of rural women in the Shatrah district for the period (1997-2023), and this is normal as a result of the natural increase in the population. The study also found that there is an impact of social customs and traditions in rural society, as these customs contributed to a decrease in the level of rural women’s income, which reached ( 19.7%), which is one of the most prominent problems that rural women are exposed to, along with other educational, health, and housing problems. The study also found that rural women are exposed to several different types of violence due to the influence of social customs, which requires abolishing and reducing these customs and finding appropriate solutions that contribute to and enhance Paying attention to rural women and their development.
Keywords: spatial analysis, rural women, rural development, demographic characteristics